BIOETHICS DILEMMA TOWARDS THE PRACTICE OF EUTHANASIA FROM THE PERSPECTIVE OF LAW AND INTERNATIONAL HUMAN RIGHTS - Philip Anggra; Lewiandy (CV Rewang Rencang, 2024)
This study examines the bioethical dilemma regarding the practice of euthanasia, focusing on the perspectives of law and international human rights. The study aims to answer how the discipline of bioethics views the practice of euthanasia in the context of international human rights and how the dilemma between patient autonomy and the principles of non-maleficence and beneficence is addressed within euthanasia legal policies. This research uses normative and descriptive analysis to reveal the ethical and legal implications of euthanasia, and presents policy recommendations to strengthen the protection of patient rights and medical ethics.